An Ayurvedic Critical Review on Nutritional Deficiency Disorders in Children - Singhade Sapna Raoji; Lanjewar Swati Rajkumar (International Journal of Ayurveda and Pharma Research, 2021)
Ayurveda has two basic aims i.e., first preventive aspect rather than curative method. Aahara (food) plays very important role to maintain health of a person as it is one of the three sub pillars (Tri-upastambha) of Ayurveda. Aahara is the main source of energy and nutrition, also with therapeutic value and most important during post treatment period to regain the strength of body. Aahara not only nourishes the body but also nurtures the mind and soul, hence it is called as Poornabramha and Aahara-sevana (eating food) considered as a ritual in Ayurveda. Nutrition is always a basic and essential part for mankind. It has also positive effect on growth and development with cognitive function in children. Various health problems can be prevented through nutritious diet.Malnutrition generally refers both to under nutrition and over nutrition diseases. Nutritional deficiency disorders are described in various Ayurvedic texts which can be correlated with Apatarpanajanya Vyadhis. Various Acharya of Ayurveda described diseases such as Phakka, Parigarbhika, Balashosha, Karshya etc in different Samhitas can also correlated to nutritional deficiency disorders. A critical review of these disorders provides different aspects of malnutrition and proper understanding of pathogenesis in terms of Dosha - Dushya which will give a valuable key for their effective management. This paper highlights the Ayurvedic review of nutritional deficiency related disorders in children